Influence of nonlinearity on the Bragg resonances in coupled magnon crystals - Lobanov, Nikita; Matveev, Oleg; Morozova, Maria (Luchshie medit͡s︡inskie t͡s︡entry Moskvy, 2024)
Purpose. The purpose of this paper is to investigate the effect of nonlinearity on formation mechanism and characteristics of Bragg resonances in vertically coupled magnon crystals with periodic groove system on the surface. In this paper a wave model is constructed, a nonlinear dispersion relation for surface magnetostatic waves in such a structure is obtained and the characteristics of each of the Bragg resonances are numerically studied with increasing input signal power. Methods. Theoretical methods of investigation of spin-wave excitations in a wide class of structures with ferromagnetic layers have been used. In particular, the following theoretical models have been used: coupled wave method, long-wave approximation. Results. This paper presents the results of a theoretical investigation of the effect of magnetic nonlinearity on Bragg resonances in a sandwich structure based on magnon crystals with periodic grooves on the surface separated by a dielectric layer. A mechanism for the formation of band gaps at the Bragg resonance frequencies in the presence of media nonlinearity has been revealed. It is shown that with increasing input power the frequency interval between the band gaps decreases. With increasing magnetization difference of magnon crystals, the effect of nonlinear convergence is more pronounced. Conclusion. The identified features extend the capabilities of sandwich structures based on magnon crystals for frequency selective signal processing by controlling the frequency selectivity, both via static coupling parameters, periodicity and layer magnetisation, and dynamically via the input signal power.